Emericella nidulans (4DP5), Cladosporium herbarum (7DF12) and Bacillus subtilis improve the nutritional value of palm kernel cake (PKC) through solid-state fermentation (SSF) - Lau, Sharon Yu Ling; Mardani Abdul Halim; Elaine Remi Anak Douglas Telajan; Wong, Clemente Michael Vui Ling (Malaysian Society for Microbiology, 2022)
Palm kernel cake (PKC) is a high-protein, high-energy food that is widely utilized in the animal feed business. However, the high fibre and limited amino acid content of untreated PKC were the main issues for it to be used as animal feed, particularly in non-ruminants. To improve the quality of PKC, this study combined the use of solid-state fermentation (SSF) and consortia of fungi and bacteria to treat the PKC. Methodology and results: Two fungi, Emericella nidulans (4DP5) and Cladosporium herbarum (7DF12) and three strains of bacteria, Bacillus subtilis, which were active mannanase producers, were used in different combinations to reduce the hemicellulose content and improve the crude protein content of PKC in a lab-scale solid-state fermentation. PKC inoculated separately with five types of mixed culture treatments were allowed to ferment. The fermentation conditions were 20% inoculum (w/v), 85-92% humidity, pH 7.0 and PKC particle size 0.8 mm. PKC treatments with two fungi, E. nidulans (4DP5) and C. herbarum (7DF12), as well as a fungus-bacterium combination, E. nidulans (4DP5) and B. subtilis, outperformed the other three treatments. The crude protein levels were increased by 3.34% and 1.86%, respectively, due to these treatments. Furthermore, the level of aflatoxins produced increased marginally but remained within the permissible limits. Conclusion, significance and impact of study: The treated PKC has more sugar and crude protein and less than 20 parts per billion (ppb) of aflatoxin, making it appropriate for animal consumption. The SSF technique of combining fungi and Bacilli enhanced the nutritional and market value of PKC substantially, which can be upscaled.